Restless-UCB, an Efficient and Low-complexity Algorithm for Online Restless Bandits - Wang, Siwei; Huang, Longbo; Lui, John C.S. (2020 Neural Information Processing Systems, 2020)
We study the online restless bandit problem, where the state of each arm evolves according to a Markov chain, and the reward of pulling an arm depends on both the pulled arm and the current state of the corresponding Markov chain. In this paper, we propose Restless-UCB, a learning policy that follows the explore-then-commit framework. In Restless-UCB, we present a novel method to construct offline instances, which only requires O(N) time-complexity (N is the number of arms) and is exponentially better than the complexity of existing learning policy. We also prove that Restless-UCB achieves a regret upper bound of [O]((N+M^3)T^[23]), where M is the Markov chain state space size and T is the time horizon. Compared to existing algorithms, our result eliminates the exponential factor (in M,N) in the regret upper bound, due to a novel exploitation of the sparsity in transitions in general restless bandit problems. As a result, our analysis technique can also be adopted to tighten the regret bounds of existing algorithms. Finally, we conduct experiments based on real-world dataset, to compare the Restless-UCB policy with state-of-the-art benchmarks. Our results show that Restless-UCB outperforms existing algorithms in regret, and significantly reduces the running time.